Preservation Of Local Wisdom In The Craft Of Mendong Mats Passed Down Through Generations In Blayu Village, Wajak District, Malang Regency - Ovilailia, Ekafauzia; Redjeki, Endang Sri; Rahardjo, Kukuh Miroso (Universitas Negeri Malang, 2024)
This study aims to understand the informal learning process involved in making mendong mats in Blayu Village, Wajak District, Malang Regency. It specifically examines how learning is imparted by sources of knowledge to learners as a reference for this research. This study uses a qualitative method with an ethnographic research type. Data for this research were obtained through observation, interviews, and documentation. The data collected reveal the informal learning process of mendong mat crafting conducted by information sources and learners passed down from generation to generation, as well as the stages of mendong mat making from start to finish. The results of the study indicate that the informal learning process is carried out by the people of Blayu Village from generation to generation. This is done to ensure that the local wisdom embodied in mendong mat crafting, which is a distinctive feature of Blayu Village, remains preserved. Additionally, according to mendong mat weavers, who are mostly housewives, this weaving activity is suitable for housewives because, despite engaging in weaving, they can still perform other household chores. Based on the research and discussions conducted, it can be concluded that the informal learning process of mendong mat crafting occurs through four stages: 1) Observation Stage, 2) Participation Stage in the making of mendong mats, 3) Trial Stage, and 4) Independent Crafting Stage. The informal learning of mendong mat crafting is passed down through generations in Blayu Village, representing a form of local wisdom preservation that will continue to be maintained and passed on to future generations. Based on the results of the research, the researcher suggests that mendong mat weavers continue to preserve local wisdom by providing informal learning not only to their descendants but also to other interested individuals. Future researchers are encouraged to use this study as a reference and explore broader and more interesting topics, as well as delve deeper into the local wisdom of mendong mat crafting.